PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK KELAS V SD INPRES BONTOMANAI KOTA MAKASSAR - Marnawati Marnawati; Munirah Munirah; Usman Usman; M Hajir Nonci (JIPMI (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah), 2023)
This study discusses the effect of applying the problem based learning model on thelearning outcomes of Indonesian students in class V SD Inpres Bontomanai MakassarCity. The purpose of this study was to describe the learning outcomes of Indonesianstudents before and after applying the problem based learning model for class V SDInpres Bontomanai Makassar City. This quantitative study used a one group pretestposttestresearch design. The population in this study were all students of class V SDInpres Bontomanai Makassar City, totaling 32 students. The sampling technique used isthe saturated sample technique, meaning that the entire research population is used as asample of this study as many as 32 people. The instrument used is a test to measurestudent learning outcomes in the form of a multiple choice test of 10 items. The data analysis technique used is descriptive statistical analysis and inferential analysis with the–t test. Based on the results of descriptive analysis obtained from the results of learningIndonesian language students in class V SD Inpres Bontomanai Makassar City, beforeapplying the Problem Based Learning model the average was 41.00. And after applyingthe Problem Based Learning model it was 73.67. Based on the results of inferentialstatistical analysis, the value of tcount = In the paired samples test table, = -12,057, df =29 and sig. (2 tailed) or p-value = 0.000 <0.05, thus it can be concluded that H1 isaccepted.